2015
DOI: 10.18632/oncotarget.6114
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal gene expression: a new indicator for prostate cancer patient prognosis?

Abstract: Prostate cancer continues to be a major cause of morbidity and mortality in men, but a method for accurate prognosis in these patients is yet to be developed. The recent discovery of altered endosomal biogenesis in prostate cancer has identified a fundamental change in the cell biology of this cancer, which holds great promise for the identification of novel biomarkers that can predict disease outcomes. Here we have identified significantly altered expression of endosomal genes in prostate cancer compared to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…50,51 Few of the tested markers showed decreasing transcript levels including ALIX, which was one of the most widely examined exosome markers in cancer development. 29,30,52,53 Our gene expression data correlated well with those gained from independent databases, [36][37][38][39] showing similarly reduced ALIX mRNA levels during adenoma-carcinoma sequence, which was also validated at the in situ protein level. Similar alterations between whole biopsy mRNA and protein level in epithelial compartment suggest that the majority of ALIX originated from these components.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…50,51 Few of the tested markers showed decreasing transcript levels including ALIX, which was one of the most widely examined exosome markers in cancer development. 29,30,52,53 Our gene expression data correlated well with those gained from independent databases, [36][37][38][39] showing similarly reduced ALIX mRNA levels during adenoma-carcinoma sequence, which was also validated at the in situ protein level. Similar alterations between whole biopsy mRNA and protein level in epithelial compartment suggest that the majority of ALIX originated from these components.…”
Section: Discussionsupporting
confidence: 79%
“…3,[25][26][27] ALIX has been tested widely in exosome studies of colorectal carcinoma cell cultures 9,28 and has shown diagnostic and prognostic significance in different tumors. [29][30][31] Besides testing the transcript levels, here we determined ALIX protein expression in situ in the epithelial and stromal compartment including α-smooth muscle actin (SMA)-positive cells in low-and high-grade dysplastic adenomas as well as non-metastatic and metastatic (both lymph node and distant) colorectal carcinomas with particular focus on individual Musashi1-positive cancer stem cells at the tumor front.…”
mentioning
confidence: 99%
“…Currently, APPL1 protein was found to be highly expressed in some tumor tissues such as aggressive prostate cancer tissues [15, 16]. Silencing of APPL1 resulted in a decrease in TGFβ-induced invasion of both human prostate cancer PC-3U cells and breast carcinoma MDA-MB-231 cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the expression of endosomal markers can have prognostic value in prostate cancers (Johnson et al, 2015). Here, we have shown that adaptive CME in NSCLC cells, resulting from upregulation of CLCb, increases cell migration and metastasis through a Dyn1-dependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Grb2 interacts with dynamin’s proline/arginine-rich domain (Solomaha et al, 2005). Interestingly, recent data have suggested that a tri-gene signature of high levels of expression of the early endosomal markers APPL1, EEA1, and rab5 strongly correlates with reduced survival in prostate cancer patients (Johnson et al, 2015). …”
Section: Discussionmentioning
confidence: 99%